Impact of Estradiol on Circulating Markers of Oxidative Stress among Hypertensive Postmenopausal Women with Co-morbidities - Salini, Asok; Poornima Jeyanthi, Govindaswamy (International Journal of Medical Research and Review, 2014)
Background: Oxidative stress plays a key role in the pathogenesis of several age-associated diseases. The antioxidant properties of estradiol reduce oxidative stress related complications. Menopause is typified by a drop in endogenous estradiol that might subsequently affect women’s wellbeing. Materials and Methods: 100 postmenopausal women were selected and classed into four groups. Estradiol (E2) and enzymatic antioxidant status were assessed among normotensive postmenopausal women (group-1), hypertensive postmenopausal women (group-2), hypertensive postmenopausal women with diabetes (group-3) and hypertensive postmenopausal women with renal insufficiency (group-4). Kruskal-Wallis test and correlation analysis were performed using SPSS16.0 statistical software. Results: Estradiol (E2), catalase (CAT), superoxide dismutase activity (SOD), glutathione peroxidase (GPx) and glutathione-S-transferase (GST) activities were significantly decreased in hypertensive postmenopausal women with diabetes (group-3) and hypertensive postmenopausal women with renal insufficiency (group-4) compared normotensive postmenopausal women (group-1). Catalase, glutathione peroxidise and glutathione-S-transferase activities were significantly reduced in the three experimental groups compared to normotensive control. Estradiol exhibited significant positive correlations with catalase, superoxide dismutase and glutathione peroxidase. Conclusion: Elevated oxidative stress along with drop in estradiol levels in postmenopausal women seems to be aggravated by co-morbid conditions.